PENERAPAN DIVERSIFIKASI PRODUK SEBAGAI UPAYA PENANGGULANGAN PANDEMI COVID-19 PADA KUSWINI KATERING - Kristiutami, Yuliana Pinaringsih; Ariesta, Fadli; Pirastyo, Swastono Putro (Jurnal Pendidikan dan Perhotelan (JPP), 2021)
The CoViD-19 pandemic became the most impactful disease in 2020, the CoViD-19 pandemic impacted various sectors of the world economy, one of which was a catering business that suffered losses due to the cancellation of orders due to government regulations prohibiting large gatherings of people, including Kuswini catering Bandung. This research aims to find out the impact that CoViD-19 has had along with countermeasures made in the application of product diversification in Kuswini Catering. The methods used in this study are qualitative descriptive with data retrieval techniques obtained from observations during the CoViD-19 pandemic interviews with sources namely business owners and documentation that can support this research that the authors successfully collected during the study. The results of the research have been conducted stated that the application of diversification in the Kuswini catering business is considered successful because the countermeasure efforts are classified as successful by diversifying products in various aspects of the product and able to minimize the impact of CoViD-19 on Kuswini catering.